Whither the West? international law in Europe and the United States - Giorgetti, Chiara 1970-; Verdirame, Guglielmo ca. 20./21. Jh (ASIL studies in international legal theory, 2021)
On a variety of international legal matters, relations between the US and European countries are evolving and even diverging. In an ever-changing world, understanding the reasons for this increasing dichotomy is fundamental and has a profound impact on our understanding of world dynamics and globalization and, ultimately, on our awareness of where the West is going. This interdisciplinary volume proposes new frameworks to understand the differences in approach to international law in the US and Europe. To explain the theoretical and historical underpinnings of the diverging views, the expert essays present new research and develop innovative conclusions. They assess and explore issues such as the idea of sovereignty, constitutional law, the use of force, treaty law and international adjudication. Leading authorities in different disciplines including law and political science, the contributors engage in a new dialogue and develop a new discourse on inter-Atlantic views